Environmental Carrying Capacity Base on Land Balance to Support Geotourism Programs in the Karst Area of South Malang - SUTANHAJI, Alexander Tunggul; SUSILO, Adi; SUNARYO, SUNARYO; SUYADNYA, I Wayan; ISHAQ, Bashori (Journal of Environmental Management and Tourism; Vol 10 No 8 (2019): JEMT Volume X Issue 8(40) Winter 2019, 2020)
Environmental carrying capacity is very much needed in areas that will be developed for geotourism, such as the South Malang Karst Area. Even though this area has a good geodiversity, biodiversity and cultural diversity to be developed into geotourism, it is necessary to know how the carrying capacity of the environment in this region supports the sustainability of this geotourism. This study aims to assess the environmental carrying capacity based on land balance in the South Malang Karst Area, which consists of 8 districts, in supporting the sustainability of geotourism. The method used in this research is a descriptive method that refers to the Regulation of the Minister of Environment of the Republic of Indonesia Number 17 of 2009 concerning Guidelines for Determination of Environmental Support Capacity in Regional Spatial Planning, by comparing the comparison of land with land requirements in South Malang. The results of the analysis show that the total cultivated land in the South Malang Karst Area of 10,519.41 hectares produced a total production value of IDR 731.3 billion. While the total land requirement to meet the population and tourists at the moment is 156,264.03 hectares or 145,744.61 less than what is available. Where the Status of Environmental Capability of each district is an overall deficit.